Optimizing PKPU in The Reconstruction of Debt Restructuring Mechanisms Based on Preventive Principles Against Liquidation in Bankruptcy Law - Patar Bronson Sitinjak; Riswadi Riswadi (CV. Green Publisher Indonesia, 2026)
The development of modern bankruptcy law has led to a paradigm shift from a liquidation approach to debt restructuring oriented toward business sustainability. The Suspension of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang/PKPU) in the Indonesian legal system is designed as a mechanism that provides negotiation space for debtors and creditors to achieve peace through restructuring. Implementation practices demonstrate a mismatch between normative objectives and empirical reality, in which PKPU often ends in bankruptcy; thus, its preventive function has not been optimally implemented. This study aims to analyze the normative construction of PKPU, identify implementation problems that cause distortion of the restructuring function, and formulate a reconstruction model based on preventive principles. The research method used is normative legal research with a statutory, conceptual, and comparative approach. The analysis is conducted on Law Number 37 of 2004 concerning Bankruptcy and PKPU, modern bankruptcy legal doctrine, and preventive restructuring practices in other legal systems. The results of the study indicate a liquidation bias influenced by procedural design, the dominance of creditor interests in the voting mechanism, limited time for restructuring, and the absence of an adequate business feasibility assessment mechanism. Reconstruction is necessary through strengthening the preventive paradigm, reformulating the application threshold, implementing viability assessments, and balancing voting mechanisms to increase the chances of successful restructuring. Optimizing the PKPU is expected to strengthen the business rescue function, maintain going-concern value, and create a balance between economic efficiency and substantive justice within the Indonesian bankruptcy legal system.